Development and application of a quadruplex TaqMan fluorescence quantitative PCR typing method for Streptococcus suis generalis, type 2, type 7 and type 9 - Wang, Haojie; Chen, Jianxing; Sun, Yue; An, Tongqing; Wang, Yue; Chen, Hongyan; Yu, Changqing; Xia, Changyou; Zhang, He (Frontiers in Cellular and Infection Microbiology, 2024)
IntroductionStreptococcus suis (SS) is one of the most important pathogens causing major economic losses in the global pig farming industry and is a serious threat to public health safety. It has multiple serotypes, with poor cross-protection between serotypes, and effective typing methods are lacking.MethodsIn this study, a quadruplex TaqMan fluorescence quantitative PCR assay that can differentiate between Streptococcus suis types 2, 7 and 9 was developed using the gdh gene, a generic gene for Streptococcus suis, and cps2J, cps7H and cps9J, genes encoding podocarp-associated genes for types 2, 7 and 9, respectively, as targets.ResultsThe method is specific enough to accurately type Streptococcus suis pigmentosus without detecting non-target pathogens (Escherichia coli, Pasteurella multocida, Staphylococcus aureus, Streptococcus agalactiae, Streptococcus pneumoniae and et al). The sensitivity was high, with a minimum lower detection line of 10 copies for P-SS and P-SS9, and 100 copies for P-SS2 and P-SS7. The standard curves generated showed good linearity with R2 of 0.999, 0.999, 0.997 and 0.998 respectively. The repeatability was good, with coefficients of variation between batch to batch and batch to batch tests ranging from 0.21% to 1.10%. Testing of 156 samples yielded 68 positive and 88 negative samples, of which the positive rate of SS was 5.77% (9/156), SS2 was 20.51% (32/156), SS7 was 8.33% (13/156) and SS9 was 9.6% (15/156), which was in line with the existing fluorescent quantitative PCR assay of 93.75%~100%, which was higher than the detection rate of conventional PCR.DiscussionThe quadruplex TaqMan fluorescence quantitative PCR method of Streptococcus suis generic, type 2, 7 and 9 established in this study can accurately differentiate the three serotypes of Streptococcus suis that currently have high prevalence and pathogenicity, which is of great importance for accurate clinical prevention and treatment, epidemiological investigation and vaccine development.